Intellectual capital components and its relationship to microfinance institutions' performance: the moderating effect of institutions specification / Maryam Jameelah Hashim ...[et al.] - Hashim, Maryam Jameelah; Muhamad Arifin, Nur Afizah; Kamarudin, Mohd Faizal; Khamiz, Mohd Rahim (Faculty of Business and Management UiTM Shah Alam, 2020)
In a majority of banking and non-banking institutions, intellectual capital (IC) is one of the prominent factors that contribute to the development of a knowledge-based economy and an increase in competitiveness. However, there is an ambiguity in whether a firm's precious resources could guarantee new strategies' success. Thus, this study was undertaken to examine the significant effect of intellectual capital on microfinance institutions' performance (MFIs). This study also examined whether the MFIs specification could have a moderating impact on the relationship between intellectual capital and MFIs' performance. The current study used the PLS-SEM to analyze the research model and found that it explains 43.6 % of the substantial amount of variance in the performance of MFIs. Theoretically, the study extends the resource-based view (RBV) in projecting the MFIs' performance. The empirical results show a significant relationship between IC and MFIs' performance for both banking and non-banking MFIs.